The Application of "off-the-shelf" Components for Building IMUs for Navigation Research - Abhayasinghe, Kahala; Murray, Iain (N/A, 2014)
Inertial measurement units (IMU) are commonly used in pedestrian and robotic navigation applications and research. Although many IMUs are commercially available, almost all of them are non-customizable and they process the collected raw data before presenting them to the user. However, this creates a limitation for researchers due to the fact that they have to rely on a set of per-processed data. Further, available resources and features such as SD card slots, wireless connectivity, available in the IMU may not suit one’s research. This paper provides a survey on availability and usage of different off-the-shelf devices to build a custom made IMU. The authors considered open source microcontroller platforms, low cost MEMS sensors and low cost accessories in this survey so that the IMUs will be affordable to many people. A range of sensors, their features, available processor options and different types of wired and wireless communication options available are discussed. Particular emphasis is made on the ability to modify or add functionality to commonly available hardware. Possible technical issues in assembling the IMU and calibrating sensors are also discussed in this paper. Technologies available for constructing a housing and mounting systems for the IMU best suited to the application are also discussed in this paper. As an example, IMUs developed and implemented by the authors with different housing designs specifically created for particular applications are presented. This survey indicated that off-the-shelf components can effectively be used to build custom-made IMUs to suit the particular research interest or application best.